Diagnosis, Treatment, and Prognosis of Syphilis in HIV Patient - Mutia Devi; Izazi Hari Purwoko; Suroso Adi Nugroho; Inda Astri Aryani; Susanti Budiamal; Putri Laksmi Karim (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Syphilis is a sexually transmitted infection caused by the bacterium Treponema pallidum (T. Palladium). Human Immunodeficiency Virus (HIV) is a virus that attacks the body's immune system, decreased the number of CD4 cells that makes the immune system decrease, and facilitates syphilis infection. Syphilis increased the risk of spreading HIV infection with skin barrier destruction. The diagnosis of syphilis is made based on a complete history, including sexual history, clinical manifestations, and examination. The treatment of syphilis with HIV and without HIV similar, penicillin is still the gold standard for syphilis treatment with HIV. Prevention of syphilis with HIV are educated, screening for syphilis and other sexually transmitted infections, as well as early detection and therapy of partners. The prognosis for syphilis in HIV is worse than for syphilis without HIV.